A no-arbitrage approach to pricing of Flexible Electricity Contracts considering transmission line rentals - Bunyi, Julius Eleazar A.
This study considers the impact of transmission line rentals on the pricing of Flexible Electricity Contracts that allows flexible scheduling of electric energy, using a no-arbitrage approach, A Flexible Electricity Contract requires the buyer or seller to schedule its amount of energy for each time interval. Given stochastic models for spot and line rental prices, this approach determines the optimal price of the Flexible Electricity Contract by determining the possible opportunities that can be performed by the buyer or seller and setting the price of the contract such that there is no arbitrage. The stochastic spot prices are modeled using autoregressive models. On the other hand, stochastic line rental prices are modeled using simple linear regression, with spot prices as the predictor variable. Based on the said stochastic models for the spot prices and line rental prices, the optimal contract price is determined using Monte Carlo simulation. Simulations are conducted using spot and line rental price information from the Philippine Wholesale Electricity Spot Market. Analysis performed in this study show that the transmission line rentals have a significant impact in the pricing of Flexible Electricity Contracts. Furthermore, this study also considered the impact of daily and hourly scheduling provisions on the contract prices.